Beliefs about age-related changes in physical functioning across the adult life span and their relationship with physical activity levels of older adults. Issue 4 (4th July 2018) - Lineweaver, Tara T; Kugler, Jennifer; Rabellino, Alessandra; Stephan, Yannick
ABSTRACT: Physical activity declines across the adult life span despite the well-established links between physical activity and health-related, psychological, cognitive, and social benefits. We contrasted the beliefs young and older adults hold about how aging affects both physical abilities and physical activity and determined whether older adults' beliefs about physical aging relate to their engagement in physical activity. Using visual rating scales, 56 young and 49 community-dwelling older adults indicated the extent to which a typical woman or typical man aged 20–90 possesses six different physical abilities and engages in three different types of physical activity. Stereotypes of physical aging were ability- and activity-specific, and older adults endorsed more positive views than their younger peers. Stereotypical beliefs predicted older adults' engagement in moderate-intensity activity. This study offers intriguing avenues for future research and suggests that better understanding physical aging stereotypes may contribute toward designing interventions that promote lifelong physical activity.